Innovative Technology Added Value in Reducing Rice Yield Gap in Tidal Land - Hutapea Yanter (EDP Sciences, 2021)
Ameliorant, one of innovative technology, is actually able to accelerate the weathering of rice straw and grass. Other than that, it can also improve soil structure and increase soil pH. This study aims to analyze the added value of using innovative technology in reducing rice yield gaps in tidal land. It involved the Banjar Harum I and Banjar Sari Farmer Groups in Pinang Banjar Village, Sungai Lilin District, Musi Banyuasin, South Sumatra during the dry season of 2020 in an area of 45 ha. The ameliorant used was 5 liter/ha of bio-decomposer and 1 t/ha lime (dolomite). The results showed that the application of bio-decomposer and dolomite produced 3,617 and 3,283 kg/ha Harvested Dry Grain (HDG) respectively of the farmer groups as compared to 1,700 kg/ha of local farmers using no ameliorant. The added value of the innovative technology use is IDR 9,126,000 and IDR 7,408,440/ha, with MBCR of 2.15 and 1.25, respectively. In the wet season of 2020, the use of bio-decomposers and dolomite can reduce yield gaps by 17.74 and 14.38%, respectively, with the potential productivity of Inpari 42.